THE USE OF GAME-BASED TECHNOLOGIES IN HIGHER PEDAGOGICAL EDUCATION: PEDAGOGICAL PROBLEMS AND SOLUTIONS - Umarov Nurbek Irkinovich (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article explores the theoretical and practical foundations of using game-based technologies in higher pedagogical education, focusing on their integration into the educational process, their effectiveness, and the existing challenges and possible solutions. Game-based learning serves as an important methodological tool for enhancing students’ motivation, communication culture, creative thinking, and active participation in learning. The paper analyzes the psychological and pedagogical mechanisms that make game-based technologies effective and discusses how they align with modern didactic principles and learner-centered approaches in teacher education.